SOLVE ABEL’S INTEGRAL EQUATION USING POINT INTERPOLATION MESHLESS METHOD - Nahdh. S .m. Al-saif (مجلة جامعة الانبار للعلوم الصرفة, 2018)
In this paper the numerical method for solving Abel,s integral equation are introduced ,this method is based on point interpolation meshless method. Also Radial basis function, zeros of the shifted Legendre polynomial as the collocation points utilized to apply for solving Abel,s integral equation of the first and second kind .The result of numerical experiment show that the numerical scheme is very effective and convenient of this method.